Protocol to perform polysome profiling in primary differentiating murine adipocytes - Mirian Krystel De Siqueira; Zaynab Nouhi; Yutian Zhao; Siqi Wang; Xinshu Xiao; Xia Yang; Laura Hulea; Claudio J. Villanueva (STAR Protocols)
Summary: Here, we present a protocol for polysome profiling in differentiating adipocytes from the mouse stromal vascular fraction. We describe steps for lysate preparation, ultracentrifugation through sucrose gradients, mRNA isolation, RNA sequencing, and motif enrichment. This protocol enables the analysis of actively translating mRNAs and translational gene regulation by isolating polysome-bound mRNA, revealing insights into protein synthesis during adipogenesis or stimuli responses. Applications include studying translational control in adipocytes, metabolic diseases, and obesity, linking translational regulation to cellular and metabolic phenotypes.For complete details on the use and execution of this protocol, please refer to De Siqueira et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.